PO147 Myelin oligodendrocyte glycoprotein-antibody disease in the uk. (1st December 2017) - Raza, Naheed; Jurynczyk, Maciej; Everett, Rosie; Woodhall, Mark; Tackley, George; Jacob, Anu; Vincent, Angela; Isabel Leite, M; Waters, Patrick; Palace, Jacqueline
Abstract : Background: Myelin Oligodendrocyte Glycoprotein antibody (MOG-Ab) disease has been recently proposed as an entity distinct from multiple sclerosis and Aquaporin-4-Ab neuromyelitis optica, but the clinical data has been derived from small and highly selected cohorts. Objective: The Oxford Autoimmune Neurology group are the only laboratory offering a MOG-Ab assay in the UK and thus able to audit the clinical features of this disease in a national cohort. Methods: Questionnaires were sent to requesting clinicians and data on 248/495 patients was obtained. Results: The MOG-Ab cohort consisted of 57% females, a mean onset age of 30.1 years (33%≤16 years), with a median disease duration of 26 months (range 0–492). There was no ethnic bias. Unilateral or bilateral optic neuritis was the commonest onset presentation (55%), followed by longitudinal extensive transverse myelitis (13%), acute disseminated encephalomyelitis (13%), simultaneous optic neuritis and transverse myelitis (9%), and short transverse myelitis (4%). 44% were relapsing and disability increased with the number of attacks (p<0.01). Recovery from the onset attack predicted long-term disability (p<0.01). Both disability at last follow-up and recovery from the onset attack worsened with the age at onset (p=0.03 and p=0.02, respectively). Longer immunosuppression following the onset attack was associated with a lower risk of relapse (p<0.05). Conclusions: Clinical outcomes in MOG-Ab disease depend on the age at onset, recovery from the onset presentation and duration of immunosuppression after the onset attack.